Association of Symptoms and Mode of Transportation to Emergency Department in Patients With Acute Coronary Syndrome. Issue 2 (March 2023) - Davis, Leslie L.; McCoy, Thomas P.; Riegel, Barbara; McKinley, Sharon; Doering, Lynn V.; Moser, Debra K.
Abstract : Background: Patients with acute coronary syndrome (ACS) with symptoms matching their expectations of a heart attack are more likely to use emergency medical services (EMS) than not. Objective: To determine whether presenting symptom clusters are associated with EMS use in ACS patients and if EMS use or symptom clusters are associated with prehospital delay. Methods: This secondary analysis used data from the PROMOTION trial, a randomized clinical trial that enrolled 3522 subjects with a history of or at risk for ACS from 5 sites in the United States, Australia, and New Zealand. Subjects were randomized to usual care or an educational intervention to reduce prehospital delay. During the 2-year follow-up, subjects admitted for ACS were asked about symptoms, time of symptom onset, and mode of transportation to the hospital. Symptoms were grouped into classic ACS, pain symptoms, and stress symptoms clusters. Results: Of 3522 subjects enrolled, 331 sought care for ACS during follow-up; 278 had transportation mode documented; 121 (44%) arrived via EMS. Classic ACS plus pain symptoms (adjusted odds ratio [AOR], 2.66; P = .011), classic ACS plus stress symptoms (AOR, 2.61; P = .007), and classic ACS plus both pain and stress symptoms (AOR, 3.90; P = .012) were associated with higher odds of EMS use versus classic ACS symptoms alone. Emergency medical services use resulted in a 68.5-minute shorter median delay ( P = .002) versus non-EMS use. Symptom clusters were not predictive of delay time in the adjusted model ( P = .952). Discussion: Although chest symptoms were the most prevalent symptoms for most (85%), the combination of classic ACS symptoms with other symptom clusters was associated with higher EMS use. Further research is needed to determine whether a combination of symptom clusters helps patients correctly interpret ACS symptoms to better understand how symptom clusters influence EMS use.